Concurrent phone texting alters crossing behavior and induces gait imbalance during obstacle crossing - Chen, Szu-Hua; Lo, On-Yee; Kay, Taylor; Chou, Li-Shan (Gait & posture, 2018)
•Conservative obstacle-crossing gait was adopted with concurrent phone texting.•The gait was accompanied by a closer leading foot placement to the obstacle.•Perturbed gait balance control in the frontal plane during crossing was detected. Texting during walking has become a very common daily activity and could alter gait performance, especially during locomotion when additional visual attention is demanded, such as obstacle crossing. The purpose of this study was to examine biomechanical changes in obstructed gait characteristics while engaging in a phone texting activity. Gait analyses were performed on ten young healthy adults under the following two tasks: 1) walking and crossing an obstacle set at a 10% of the subject’s height and 2) walking and crossing an obstacle while responding to a text message. Whole body motion data were collected with a 10-camera motion capture system. Our data demonstrated that a conservative gait pattern was adopted while performing texting when approaching and crossing over the obstacle, which was indicated by slower walking speeds and greater toe-obstacle clearances. This gait pattern was, however, accompanied by a greater body sway in the frontal plane during crossing, which could be an indication of perturbed gait balance control. Increased visual-attentional demand from a concurrent phone texting could negatively impact young pedestrians’ safety during obstacle crossing.